A magyarországi idegenforgalmi régiók fejlettségének, versenyképességének és leterheltségének vizsgálata - Tóth, Géza; Dávid, Lóránt (Közép-Európai Közlemények, 2010)
Today, research into tourism and competitiveness is a relevant professional question. A complex and reconciled study of competitiveness, sustainable development and tourism developments is also an important interest of the economy. This study attempts to carry out the regionalisation of the GDPs of Hungary’s tourism regions and the national tourism GDP accordant to international methodologies and published in tourism satellite accounts by the Hungarian Central Statistical Office. The concentration, spatial disparities and features of these two indicators will also be examined. The competitiveness of the Hungarian counties is analysed in a multi-modal approach and, finally, a review on the load of tourism regions by applying the Tourism Penetration Index will be given.